Depiction of Social and Political Elements in Khalid Hosseini’s A Thousand Splendid Suns - Kabir Rahimi, Fawzia; Ahmad Naik, Gowhar (International Journal of Psychosocial Rehabilitation, 2021)
This research discusses the depiction ofsocial and political elements of Afghanistan during decades in Khaled Hosseini’s A Thousand Splendid Suns. The purpose of this study is to understand social and political issues. Khaled Hosseini used the novel as a tool to show the world that Afghanistan needed aid and Hosseini wanted to deliver a reflection of Afghanistan country in the past. Each decade was explained through some aspects namely social and political, cultural, educational and health.